Gut Microbiota Changes in Patients with Bipolar Depression. Issue 14 (15th May 2019) - Hu, Shaohua; Li, Ang; Huang, Tingting; Lai, Jianbo; Li, Jingjing; Sublette, M. Elizabeth; Lu, Haifeng; Lu, Qiaoqiao; Du, Yanli; Hu, Zhiying; Ng, Chee H.; Zhang, Hua; et al.
Abstract: This study aims to characterize the gut microbiota in depressed patients with bipolar disorder (BD) compared with healthy controls (HCs), to examine the effects of quetiapine treatment on the microbiota, and to explore the potential of microbiota as a biomarker for BD diagnosis and treatment outcome. Analysis of 16S‐ribosomal RNA gene sequences reveals that gut microbial composition and diversity are significantly different between BD patients and HCs. Phylum Bacteroidetes and Firmicutes are the predominant bacterial communities in BD patients and HCs, respectively. Lower levels of butyrate‐producing bacteria are observed in untreated patients. Microbial composition changes following quetiapine treatment in BD patients. Notably, 30 microbial markers are identified on a random forest model and achieve an area under the curve (AUC) of 0.81 between untreated patients and HCs. Ten microbial markers are identified with the AUC of 0.93 between responder and nonresponder patients. This study characterizes the gut microbiota in BD and is the first to evaluate microbial changes following quetiapine monotherapy. Gut microbiota‐based biomarkers may be helpful in BD diagnosis and predicting treatment outcome, which need further validations. Abstract : The gut microbiota in depressed patients with bipolar disorder is characterized, as well as its associations with queitapine monotherapy. Short‐term quetiapine treatment fails to draw the microbial ecosystem of bipolar disorder (BD) patients close to that of healthy individuals. Notably, microbial markers show powerful efficacy in distinguishing patients from healthy controls and predicting treatment outcome.